2022
DOI: 10.1103/physrevb.106.184108
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Raman-active lattice vibrations of magnetic topological insulators MnBi2Te4·n(Bi2Te3)

Abstract: bly because of the obvious difficulties in the preparation of MnBi 2 Te 4 • n(Bi 2 Te 3 ) with high index n and unavailability of samples.We have succeeded in this regard and present here the crystal structure of the members with n = 4, 5, and 6, summarize all available structural data for MnBi 2 Te 4 • n(Bi 2 Te 3 ), trace the evolution of Raman spectra of MnBi 2 Te 4 • n(Bi 2 Te 3 ) that embraces all n from 0 to 6 as well as n = ∞ (Bi 2 Te 3 ), and provide a thorough analysis of the obtained Raman data. II. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The growth from the melt is done by cooling the stoichiometric melt of the targeted phase through its melting temperature [ 3 , 4 , 13 , 16 , 32 , 35 , 57 , 59 , 60 ]. Modified Bridgman and vertical Bridgman methods were used.…”
Section: The Growth Of High-quality M \Documentclass[12pt]...mentioning
confidence: 99%
See 2 more Smart Citations
“…The growth from the melt is done by cooling the stoichiometric melt of the targeted phase through its melting temperature [ 3 , 4 , 13 , 16 , 32 , 35 , 57 , 59 , 60 ]. Modified Bridgman and vertical Bridgman methods were used.…”
Section: The Growth Of High-quality M \Documentclass[12pt]...mentioning
confidence: 99%
“…Single-crystalline blocks of each phase can be isolated from the as-grown ingot. However, due to the intergrowth, especially on the high- n side, sizable pure-phase single crystals with n ≥ 4 have not been obtained even using the vertical Bridgman method, which can achieve more precise and consistent temperature control [ 60 ]. The mixture is typically heated to around 900 ○ C, where they form a homogeneous liquid.…”
Section: The Growth Of High-quality M \Documentclass[12pt]...mentioning
confidence: 99%
See 1 more Smart Citation
“…While the neighboring MBT layers prefer an antiferromagnetic (AFM) while not ferromagnetic (FM) interlayer coupling [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], leading to that the QAH effect can only be realized in oddlayered MBT and at low temperature (∼1 K) [47]. Latest experiments have shown that layered TI of Bi 2 Te 3 (BT) can be intercalated into MBT by a series of magnetic TIs of MBT•n(BT) [60][61][62][63][64][65][66][67]. Specifically, the FM interlayer coupling has been achieved by increasing BT layers [64][65][66], indicating that intercalating BT layers in MBT may be an efficient way to realize high-temperature QAH effect.…”
Section: Introductionmentioning
confidence: 99%